A content analysis of sustainability reporting: A pathway to advancing low-carbon cities development in Malaysia - Mashod, Jubaidah; Ismail, Rina Fadhilah; Fahmi, Fadzlina Mohd; Pratama, Arie (International Journal of Management and Sustainability, 2025)
Low-carbon cities represent a vital agenda of sustainable development, aligned with the United Nations Sustainable Development Goals (SDGs) and prioritized under the 12th Malaysia Plan. Although many local authorities have initiated programs to promote low-carbon development, limited secured funding remains a constraint. To attract private investment, effective communication, especially through public documents like annual reports, remains essential but is currently underutilized. Past research has found that disclosure of low-carbon initiatives by Malaysian local authorities is often limited, inconsistent, and varies widely. This is partly due to differences in how report preparers interpret and balance local priorities with global sustainability expectations. Consequently, stakeholders may face difficulties in evaluating these initiatives during the decision-making process. This study examines the annual reports of Malaysian local authorities, focusing on three objectives: to assess the comprehensiveness of disclosure, evaluate compliance with reporting guidelines, and identify variations in reporting practices. The analysis highlights similarities in core content elements but reveals differences in how low-carbon initiatives are reported, the level of compliance with guidelines, stakeholder inclusion, and the use of financial indicators. These variations reflect the differing contexts, capacities, and strategic priorities of local jurisdictions. The study offers insights into the current state of sustainability reporting among Malaysian local authorities and serves as a benchmark to improve transparency and consistency. It highlights the need for transparent and comprehensive reporting to meet stakeholder expectations and strengthen commitment to the SDGs, while also acting as a critical step toward securing private financing for sustainable development initiatives.